Expansion Planning of Electrical Distribution Systems Considering Voltage Quality and Reliability Criteria - Marco Israel Zuñiga Villarreal; Alexander Aguila Téllez; Narayanan Krishnan; Marcelo García (Energies)
This study aimed to assess the power capacity of electrical conductors under the long-term expansion of distribution systems over a 10-year horizon by considering voltage quality constraints and reliability indicators. The MATPOWER library in Matlab was employed, along with the IEEE 15-bus and 33-bus distribution system test cases. A 5% annual load growth was simulated for each system, which involved analyzing key parameters, such as the power loss, voltage deviation, and average failure rate. An algorithm was developed to perform a multi-criteria analysis, which provided optimal solutions for the system behavior in response to increasing demand. Given the close relationship between distribution systems and load growth, voltage quality and reliability indicators were evaluated annually to identify improvement opportunities by taking into account economic factors, implementation timelines, the replacement of electrical components, and medium- and long-term investments. The proposed algorithm recommended upgrades to electrical conductors without significantly affecting the system costs. For the initial year of the IEEE 15-bus system, enhancements were suggested for lines L1–L2, L2–L3, L3–L4, L2–L6, L3–L11, and L11–L12, which allowed the system to operate without further modifications for five years, maintained the minimum voltages above 0.95 p.u., and reduced the average failure rate while demand continued to grow.